O07-3 Work disability duration: a comparative analysis of canadian provinces. (1st September 2016) - Mcleod, Christopher; Quirke, William; Fan, Jonathan; Macpherson, Robert; Amick, Ben; Mustard, Cam; Kraut, Allen; Hogg-Johnson, Sheilah; Koehoorn, Mieke
Abstract : Objectives: This study assessed cross-jurisdictional differences in work disability duration in three Canadian provinces: British Columbia (BC), Manitoba (MB) and Ontario (ON) for the years 2007 to 2011. Methods: Comparable cohorts of injured workers in each of the three provinces were created using individual-level claims data. Comparisons were made based on number of total disability days paid per 1, 000 standardised workers and summed to reflect the cumulative disability days paid post injury at six months, six months to one year and one year overall. Analysis was conducted by injury type (e.g. strain and non-strain), occupation (e.g. registered nurses and labourers) and by sector (e.g. construction and health care). Results: The BC, MB and ON cohorts comprised of 258, 247, 70, 221 and 295, 934 injured workers respectively. Across all injuries and all occupations the number of disability days paid per 1000 injured workers over one-year post injury was 37, 449, 28, 780 and 30, 637 in BC, MB and ON. A greater number of days were paid for strain injuries (BC: 39, 017; MB: 30, 524; ON: 30, 839) than non-strain injuries (BC: 34, 997; MB: 25, 460; ON: 30, 334). By sector, number of disability days paid in health care was markedly lower in Ontario compared to BC and MB (BC: 42, 608; MB: 39, 893; ON: 23, 557), while the number of days paid in construction was higher in ON and lowest in MB (BC: 43, 759; MB: 35, 268; ON: 51, 446). In trends over time for all injuries and occupations, disability duration levels were constant in MB, increasing in BC, and decreasing in ON. Conclusions: Large differences in cumulative number of disability days paid were observed across jurisdictions and sector. Results indicate that jurisdiction has a marked effect on duration of work-disability by injury type and sector across Canadian provinces which may be related to differences in policies and approaches to work disability management.